The Chronicles of Vladimir Tod : tenth grade bleeds / 3. - Brewer, Heather (Vladimir Tod, 2009)
Tenth grade does not bring any relief to Vlad who is finding it increasingly difficult to resist feeding on his classmates and to avoid the evil vampire D'Ablo who wants to drain his powers.